Comparative Antidiabetic Studies of Leaves of Ipomoea carnea and Grewia asiatica on Streptozotocin Induced Diabetic Rats - kumar, Shankul (International Journal of Pharmaceutical & Biological Archive, 2012)
Comparative Antidiabetic Studies of Leaves of Ipomoea carnea and Grewia asiatica on Streptozotocin Induced Diabetic Rats